Key parameters of efficient phosphor-filled luminescent down-shifting layers for photovoltaics - Solodovnyk, Anastasiia; Lipovsek, Benjamin; Riedel, Daniel; Forberich, Karen; Stern, Edda; Batentschuk, Miroslaw; Krc, Janez; Topic, Marko; Brabec, Christoph (Journal of Optics A-Pure and Applied Optics, 2017)
Spectral management is one of the promising ways to increase the efficiency of modern photovoltaic devices. We study the performance of phosphor-filled luminescent down-shifting (LDS) layers. We focus on four powder phosphors with refractive indices in the range of 1.66-1.84 and similar particle size distributions. Using experimental characterization as well as 3D optical simulations, we identify key parameters of the phosphor particles and LDS layers that primarily affect the optical transmittance, absorptance, and photoluminescence quantum yield of the layers. We investigate the influence of the medium located beneath the LDS layer and reveal a strong increase in the performance when the layer is applied directly onto the solar cell. Finally, the optimal combination of the particle, binder and layer parameters that render the highest performance of the LDS layers are also indicated and discussed. © 2017 IOP Publishing Ltd.
Keywords: absorptance; phosphors; photoluminescence quantum yield; photovoltaics; transmittance